Wave-absorbing material as well as preparation method and application thereof

Through ball milling, magnetic separation and heat treatment processes, the magnetite powder in the iron-rich nickel copper slag is deeply processed, which improves its wave absorption performance, solves the problem of resource utilization of magnetite powder recovery, and realizes the frequency band 2~18GHz The regulation of absorbing performance and cost reduction have promoted the recycling of waste slag resources.

CN119144281APending Publication Date: 2024-12-17LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411274004.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover and reuse magnetite powder in iron-rich nickel-copper slag, resulting in waste of resources and high economic costs.

Method used

The recovered magnetite powder is deeply processed through ball milling, magnetic separation and heat treatment processes to improve its wave absorption performance and make it a Fe3O4-based wave absorption agent, suitable for composite wave absorption materials.

Benefits of technology

It has achieved improvement in the absorption performance of magnetite powder, and can regulate its absorption performance in the 2-18GHz frequency band, greatly expand its application range, reduce production costs, and promote the recycling of waste slag resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005041671610000021
    Figure BDA0005041671610000021
  • Figure BDA0005041671610000071
    Figure BDA0005041671610000071
  • Figure FDA0005041671470000011
    Figure FDA0005041671470000011
Patent Text Reader

Abstract

The invention belongs to the technical field of wave-absorbing materials, and particularly relates to a wave-absorbing material and a preparation method and application thereof. The preparation method of the wave-absorbing material provided by the invention comprises the following steps: sequentially carrying out ball milling, magnetic separation and heat treatment on magnetite powder to obtain the wave-absorbing material, the magnetite powder is recycled from waste residues, and the average particle size of a product obtained after ball milling is 0.5-20 microns. According to the method, the magnetite powder recycled from the waste residues is simply treated, so that the wave absorbing performance of the Fe3O4 crystals derived from the waste residues can be greatly improved, the effective wave absorbing frequency band of the Fe3O4 crystals can be regulated and controlled within the frequency band range of 2-18 GHz, and the Fe3O4-based wave absorbing agent which can be applied to industrial production is prepared from the Fe3O4-based wave absorbing agent. According to the method for converting the waste residue derived Fe3O4 crystals into the wave-absorbing material with the excellent wave-absorbing performance, large-scale and low-cost production can be achieved, and the application range of the magnetite powder recycled from the waste residues is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a wave absorbing material and a preparation method and application thereof. Background Art

[0002] With the mining of nickel and copper mines, a large amount of iron-rich nickel-copper slag will be produced. A large amount of waste slag not only occupies land, but also pollutes the environment, and causes a huge waste of resources. The total iron (TFe) content in the waste slag can reach an average of more than 40%. If it can be recovered, extracted and reused, it can not only dispose of a large amount of stockpiled waste slag, but also create huge economic value. At present, the iron in the waste slag is mainly extracted in the form of magnetite by the molten oxidation method, but how to economically and efficiently reuse the extracted and recovered magnetite powder has become a bottleneck problem in the recycling of waste slag resources. The conventional treatment method is to use it as an iron concentrate for steel smelting, but the recovered magnetite powder has a high impurity content. If it is to be used in steel smelting, it needs to be treated with impurities, which leads to increased costs and poor economic efficiency, making it difficult to promote industrialization.

[0003] Exploring new applications of magnetite powder recovered from iron-nickel-copper-rich slag is a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, the present invention provides an absorbing material and a preparation method and application thereof. The present invention improves the absorbing performance of magnetite powder recovered from iron-nickel-copper-rich slag after processing, and can be used as a Fe3O4-based absorbing agent.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing an absorbing material, comprising the following steps:

[0006] The magnetite powder is subjected to ball milling, magnetic separation and heat treatment in sequence to obtain the microwave absorbing material;

[0007] The magnetite powder is magnetite powder recovered from waste slag, and the average particle size of the product after ball milling is 0.5-20 μm.

[0008] Preferably, the ball milling is wet ball milling, and the dispersant of the wet ball milling includes ethanol; the rotation speed of the ball mill is 200-300 r / min, and the ball milling time is 3-15 h.

[0009] Preferably, the grinding balls used for ball milling are large grinding balls, medium grinding balls and small grinding balls; the diameter of the large grinding balls is 8-12 mm, the diameter of the medium grinding balls is 5-7 mm, and the diameter of the small grinding balls is 2-4 mm; the mass ratio of the large grinding balls, medium grinding balls and small grinding balls is 1:9-11:18-22; the material-ball ratio of the ball mill is 1:10-30.

[0010] Preferably, the intensity of the magnetic separation is 50 to 300 mT;

[0011] Before the magnetic separation, the process also includes: dispersing the ball-milled product in water to obtain a dispersion.

[0012] Preferably, the magnetic separation can be repeated 2 to 6 times.

[0013] Preferably, the product obtained by magnetic separation is dried before the heat treatment, and the drying temperature is 75 to 85° C. and the time is 8 to 16 hours.

[0014] Preferably, the temperature of the heat treatment is 500-900° C., the holding time is 1-3 hours, and the heating rate to the temperature required for the heat treatment is 4-6° C. / min.

[0015] Preferably, the magnetite powder comprises the following components in percentage by mass:

[0016]

[0017] The present invention also provides an absorbing material prepared according to the preparation method described in the above technical solution, comprising a magnetite phase and a pyroxene phase; the mass percentage of the magnetite phase in the absorbing material is 70-85%;

[0018] The average particle size of the wave absorbing material is 0.5-20 μm.

[0019] The present invention also provides the use of the absorbing material described in the above technical solution as a Fe3O4-based absorbing agent in a composite absorbing material.

[0020] The present invention provides a method for preparing an absorbing material, comprising the following steps: subjecting magnetite powder to ball milling, magnetic separation and heat treatment in sequence to obtain the absorbing material; the magnetite powder is magnetite powder recovered from waste slag, and the average particle size of the product after ball milling is 0.5 to 20 μm. The present invention can greatly improve the absorbing performance of Fe3O4 crystals derived from waste slag by simply treating the magnetite powder recovered from waste slag, and can regulate its effective absorbing frequency band within the frequency band of 2 to 18 GHz, so as to prepare it into a Fe3O4-based absorber that can be used in industrial production. The method provided by the present invention for converting Fe3O4 crystals derived from waste slag into absorbing materials with excellent absorbing performance can be produced in large quantities and at low cost, which expands the application range of magnetite powder recovered from waste slag and can better recycle solid waste slag. DETAILED DESCRIPTION

[0021] The present invention provides a method for preparing a wave absorbing material, comprising the following steps:

[0022] The magnetite powder is subjected to ball milling, magnetic separation and heat treatment in sequence to obtain the wave absorbing material.

[0023] In the present invention, the magnetite powder is magnetite powder recovered from waste slag. In the present invention, the magnetite powder is preferably recovered from pyrometallurgical nickel smelting waste slag using a molten oxidation process. In the present invention, the average particle size of the magnetite powder is preferably <74 μm. In the present invention, the magnetite powder preferably includes the following components in percentage by mass in terms of element oxide form: 45-60% FeO, 10-25% SiO2, 3-7% MgO, 3-7% CaO and 1-2% impurities. In the present invention, the impurities preferably include one or more of Ni, Co, Cu and Al. In the present invention, the magnetite powder preferably includes a magnetite phase (Fe3O4), a pyroxene phase (CaMgSi2O6) and an impurity phase; the mass percentage of the magnetite phase in the magnetite powder is preferably 50-65%, more preferably 55-60%; the mass percentage of the pyroxene phase in the magnetite powder is preferably 30-45%, more preferably 35-40%.

[0024] In the present invention, the ball mill is preferably a wet ball mill, and the dispersant of the wet ball mill is preferably ethanol, and the ethanol is preferably analytically pure. In the present invention, the rotation speed of the ball mill is preferably 200-300r / min, more preferably 250-280r / min; the time of the ball mill is preferably 3-15h, more preferably 6-12h. In the present invention, the grinding balls for the ball mill are preferably zirconium balls, and the grinding balls for the ball mill are preferably large grinding balls, medium grinding balls and small grinding balls; the diameter of the large grinding balls is preferably 8-12mm, more preferably 10mm; the diameter of the medium grinding balls is preferably 5-7mm, more preferably 6mm; the diameter of the small grinding balls is preferably 2-4mm, more preferably 3mm; the mass ratio of the large grinding balls, the medium grinding balls and the small grinding balls is preferably 1:5-11:10-22, more preferably 1:10:20; the material-ball ratio of the ball mill is preferably 1:10-30, more preferably 1:15-25, and further preferably 1:20.

[0025] In the present invention, the ball milling is preferably carried out in a planetary ball mill. In the present invention, the average particle size of the product after ball milling is 0.5 to 20 μm, preferably 1 to 10 μm, and more preferably 3 to 6 μm. The present invention limits the material-to-ball ratio and the ball milling time of ball milling so that the product after ball milling reaches a certain particle size, thereby achieving effective separation of the magnetite phase and the pyroxene phase, which is beneficial for subsequent magnetic separation to make the mass percentage of the magnetite phase in the absorbing material 70 to 85%, thereby improving the absorbing performance of the absorbing material.

[0026] In the present invention, the magnetic separation preferably further includes: dispersing the ball-milled product in water to obtain a dispersion. The present invention preferably washes the ball-milled product with water before dispersion. The present invention uses water to degas the dispersant ethanol. In the present invention, the dispersion is preferably carried out under ultrasonic conditions, and the power of the ultrasound is preferably 100 to 150w, more preferably 110 to 120w; the time of the ultrasound is preferably 20 to 40min, more preferably 25 to 30min. The present invention avoids agglomeration of the powder after ball milling by dispersion, which is beneficial to the subsequent magnetic separation.

[0027] In the present invention, the magnetic separation is preferably carried out in a wet magnetic separator, and the dispersion is preferably passed into the wet magnetic separator, and the flow rate of the passing is preferably 300-500 mL / min, 350-450 mL / min. In the present invention, the intensity of the magnetic separation is preferably 50-300 mT, more preferably 150-200 mT.

[0028] In the present invention, the magnetic separation can be preferably repeated, and the number of repetitions is preferably 2 to 6 times, and more preferably 3 to 5 times. The purpose of repeating the magnetic separation in the present invention is to make the magnetite and silicate gangue more fully separated and obtain the recovered magnetite powder with higher Fe3O4 grade.

[0029] In the present invention, the product obtained by magnetic separation is preferably dried before the heat treatment. In the present invention, the drying temperature is preferably 75-85°C, more preferably 80°C; the drying time is preferably 8-16h, more preferably 10-12h.

[0030] In the present invention, the temperature of the heat treatment is preferably 500-900°C, more preferably 600-800°C; the holding time of the heat treatment is preferably 1-3h, more preferably 2h. In the present invention, the heating rate to the temperature required for the heat treatment is preferably 4-6°C / min, more preferably 5°C / min. In the present invention, the heat treatment is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably nitrogen. In the present invention, the heat treatment is preferably carried out in a tube furnace. In the present invention, the heat treatment will not change the phase composition of the product, but only eliminate crystal defects.

[0031] In the present invention, after the heat treatment, the heat treatment process preferably further comprises: cooling the heat treated product. In the present invention, the temperature after cooling is preferably room temperature, and the room temperature is preferably 20 to 35° C., more preferably 25 to 30° C. The present invention has no special requirements for the cooling method, as long as the desired temperature can be reached.

[0032] In the present invention, magnetite crystals and dielectric silicate materials in magnetite powder are extracted and recovered from pyrometallurgical nickel smelting waste slag (iron-nickel-rich slag) through a molten oxidation process, and are inlaid, staggered and mutually wrapped. The present invention adjusts the ratio between the magnetic component and the dielectric component in the recovered magnetite powder through grinding and magnetic separation, and uses a heat treatment process to repair and eliminate its crystal microscopic features (crystal defects, intercrystalline stress, etc.), so that the electromagnetic matching in the material is optimized, the wave absorbing performance is improved, and the material has wave absorbing capabilities in different microwave frequency bands.

[0033] The present invention also provides an absorbing material prepared by the preparation method described in the above technical solution, comprising a magnetite phase and a pyroxene phase; the mass percentage of the magnetite phase in the absorbing material is 70-85%, preferably 75-80%. In the present invention, the average particle size of the absorbing material is 0.5-20 μm, preferably 0.8-10 μm. In the present invention, the absorbing material has good absorbing performance in the C band, X band and Ku band.

[0034] The present invention also provides the use of the absorbing material described in the above technical solution as a Fe3O4-based absorbing agent in a composite absorbing material. In the present invention, the composite absorbing material preferably includes a rubber absorbing sheet or a absorbing coating.

[0035] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0036] Example 1

[0037] 10g of nickel slag-derived magnetite powder (recovered from pyrometallurgical nickel smelting waste slag by melt oxidation process) was placed in a ball mill of a planetary ball mill, and large, medium and small zirconium balls with a mass ratio of 1:10:20 were used as grinding balls, the sizes of the large, medium and small zirconium balls were 10mm, 6mm and 3mm respectively, and the material-to-ball ratio was 1:20. Analytical pure alcohol was used as grinding liquid, and the ball milling was carried out at a speed of 300r / min for 6h; the material with an average particle size of 3μm after ball milling was washed with water, mixed with water, and ultrasonically oscillated for 30min at a power of 120W to obtain a dispersion;

[0038] The dispersion was passed into a wet magnetic separator at a flow rate of 400 mL / min and magnetically separated at a magnetic separation intensity of 150 mT. The magnetic powder recovered by magnetic separation was added with water and magnetic separation was repeated 5 times. The mixture was then dried at a constant temperature of 80°C in a vacuum drying oven for 8 h to obtain an intermediate, which was marked as S1.

[0039] The intermediate was loaded into a corundum magnetic boat, placed in a horizontal tube furnace, heated to 700°C at a heating rate of 5°C / min under a nitrogen protective atmosphere, kept at this temperature for 2 hours for heat treatment, cooled to room temperature at a cooling rate of 5°C / min, and the sample was taken out to obtain a nickel slag derived Fe3O4 absorbing material, recorded as S2.

[0040] Example 2

[0041] 10g of nickel slag-derived magnetite powder (recovered from pyrometallurgical nickel smelting waste slag by melt oxidation process) was placed in a ball mill of a planetary ball mill, and large, medium and small zirconium balls with a mass ratio of 1:10:20 were used as grinding balls, the sizes of the large, medium and small zirconium balls were 10mm, 6mm and 3mm respectively, and the material-to-ball ratio was 1:20. Analytical pure alcohol was used as grinding liquid, and the ball milling was carried out at a speed of 300r / min for 3h; the material with an average particle size of 6μm after ball milling was washed with water, mixed with water, and ultrasonically oscillated for 30min at a power of 140W to obtain a dispersion;

[0042] The dispersion was passed into a wet magnetic separator at a flow rate of 400 mL / min and magnetically separated at a magnetic separation intensity of 100 mT. The magnetic powder recovered by magnetic separation was added with water and magnetic separation was repeated three times. The mixture was then dried at a constant temperature of 80°C in a vacuum drying oven for 12 h to obtain an intermediate, which was labeled as S1.

[0043] The intermediate was loaded into a corundum magnetic boat, placed in a horizontal tube furnace, heated to 500°C at a heating rate of 5°C / min under a nitrogen protective atmosphere, kept warm for 3 hours for heat treatment, cooled to room temperature at a cooling rate of 5°C / min, and the sample was taken out to obtain a nickel slag derived Fe3O4 absorbing material, recorded as S2.

[0044] Example 3

[0045] 10g of nickel slag-derived magnetite powder (recovered from pyrometallurgical nickel smelting waste slag by melt oxidation process) was placed in a ball mill of a planetary ball mill, and large, medium and small zirconium balls with a mass ratio of 1:10:20 were used as grinding balls, the sizes of the large, medium and small zirconium balls were 10mm, 6mm and 3mm respectively, and the material-to-ball ratio was 1:20. Analytical pure alcohol was used as grinding liquid, and the ball milling was carried out at a speed of 300r / min for 12h; the material with an average particle size of 1.5μm after ball milling was washed with water, mixed with water, and ultrasonically oscillated for 30min at a power of 140W to obtain a dispersion;

[0046] The dispersion was passed into a wet magnetic separator at a flow rate of 500 mL / min and magnetically separated at a magnetic separation intensity of 200 mT. The magnetic powder recovered by magnetic separation was added with water and magnetic separation was repeated 5 times. The mixture was then dried at a constant temperature of 80°C in a vacuum drying oven for 12 h to obtain an intermediate, which was marked as S1.

[0047] The intermediate was loaded into a corundum magnetic boat, placed in a horizontal tube furnace, heated to 700°C at a heating rate of 5°C / min under a nitrogen protective atmosphere, kept at that temperature for 1 hour for heat treatment, cooled to room temperature at a cooling rate of 5°C / min, and the sample was taken out to obtain a nickel slag derived Fe3O4 absorbing material, recorded as S2.

[0048] Example 4

[0049] 10g of nickel slag-derived magnetite powder (recovered from pyrometallurgical nickel smelting waste slag by melt oxidation process) was placed in a ball mill of a planetary ball mill, and large, medium and small zirconium balls with a mass ratio of 1:10:20 were used as grinding balls, the sizes of the large, medium and small zirconium balls were 10mm, 6mm and 3mm respectively, and the material-ball ratio was 1:20. Analytical pure alcohol was used as grinding liquid, and the ball milling was carried out at a speed of 300r / min for 15h; the material with an average particle size of 1.5μm after ball milling was washed with water, mixed with water, and ultrasonically oscillated for 40min at a power of 100W to obtain a dispersion;

[0050] The dispersion was passed into a wet magnetic separator at a flow rate of 500 mL / min and magnetically separated at a magnetic separation intensity of 200 mT. The magnetic powder recovered by magnetic separation was added with water and magnetic separation was repeated 5 times. The mixture was then dried at a constant temperature of 80°C in a vacuum drying oven for 8 h to obtain an intermediate, which was marked as S1.

[0051] The intermediate was loaded into a corundum magnetic boat, placed in a horizontal tube furnace, heated to 800°C at a heating rate of 5°C / min under a nitrogen protective atmosphere, kept at that temperature for 1 hour for heat treatment, cooled to room temperature at a cooling rate of 5°C / min, and the sample was taken out to obtain a nickel slag derived Fe3O4 absorbing material, recorded as S2.

[0052] Comparative Example 1

[0053] The absorbing material was prepared according to the method of Example 1, except that the material-to-ball ratio in ball milling was 1:8, the ball milling time was 2 h, and the average particle size of the material after ball milling was 24 μm.

[0054] The phase composition, electromagnetic absorption performance parameters and particle size distribution of the intermediate S1 and the absorbing material S2 samples prepared in Examples 1 to 4 and Comparative Example 1 were characterized by X-ray diffractometer (XRD), vector network analyzer (VNA) and laser particle size analyzer. The results are listed in Table 1. The electromagnetic parameters of the samples were characterized by vector network analyzer, and the absorbing performance parameters were calculated according to the transmission line theory. Table 1 Absorption performance of absorbers S1 and S2 prepared in Examples 1 to 4 and Comparative Example 1 in different bands

[0055]

[0056] Note: The minimum reflection loss is lower than -10dB, indicating that 90% of the electromagnetic wave energy can be absorbed and the wave absorption performance is applicable; the minimum reflection loss is lower than -20dB, indicating that 99% of the electromagnetic wave energy can be absorbed and the wave absorption performance is excellent.

[0057] The intermediate S1 prepared in Example 1 exhibits wave absorbing performance in the Ku band 15-18 GHz frequency band, and the minimum reflection loss is -40 dB at 16.65 GHz; the magnetic wave material S2 prepared in Example 1 exhibits wave absorbing performance in the C band 3-8 GHz frequency band, the X band 8-12 GHz frequency band and the Ku band 12-18 GHz frequency band, and the minimum reflection loss is -39 dB at 6.9 GHz.

[0058] The intermediate S1 prepared in Example 2 exhibits wave absorbing performance in the Ku band 16.5-18 GHz frequency band, and the minimum reflection loss is -20 dB at 17.45 GHz; the magnetic wave material S2 prepared in Example 2 exhibits wave absorbing performance in the C band 4-8 GHz frequency band, the X band 8-10 GHz frequency band and the Ku band 14-18 GHz frequency band, and the minimum reflection loss is -23 dB at 4.8 GHz.

[0059] The intermediate S1 prepared in Example 3 exhibits wave absorbing performance in the Ku band 15-18 GHz frequency band, and the minimum reflection loss is -34 dB at 16.60 GHz; the magnetic wave material S2 prepared in Example 3 exhibits wave absorbing performance in the C band 3-8 GHz frequency band, the X band 8-10.5 GHz frequency band and the Ku band 13-18 GHz frequency band, and the minimum reflection loss is -30 dB at 6.8 GHz.

[0060] The intermediate S1 prepared in Example 4 exhibits wave absorbing performance in the Ku band 15-18 GHz frequency band, and the minimum reflection loss is -31 dB at 16.20 GHz; the magnetic wave material S2 prepared in Example 4 exhibits wave absorbing performance in the C band 3-8 GHz frequency band, the X band 8-12 GHz frequency band and the Ku band 12-18 GHz frequency band, and the minimum reflection loss is -18 dB at 15.8 GHz.

[0061] The intermediate S1 prepared in Comparative Example 1 exhibits wave absorbing performance in the Ku-band frequency band of 16.5-18 GHz, and the minimum reflection loss is -12 dB at 17.50 GHz; the magnetic wave material S2 prepared in Comparative Example 1 exhibits wave absorbing performance in the C-band frequency band of 2-8 GHz and the Ku-band frequency band of 14-18 GHz, and the minimum reflection loss is -13 dB at 5.5 GHz, but does not exhibit wave absorbing performance in the X-band frequency band of 8-12 GHz.

[0062] It can be seen from Table 1 that the recovered magnetite powder can be treated according to the method provided by the present invention to have good wave absorbing performance and can be used as a wave absorbing agent.

[0063] The present invention adopts ball milling, magnetic separation, and heat treatment to deeply process and remanufacture nickel slag-derived magnetite powder, change the particle size of the material powder and the Fe3O4-SiO2 ratio in the composition, improve the crystallization degree of the material, and repair crystal defects, thereby achieving a significant improvement in the wave absorption performance and frequency band regulation within the commonly used wave absorption frequency band of 2 to 18 GHz. The wave absorption performance of the nickel slag-derived Fe3O4 absorber produced by the present invention has reached or even exceeded that of the Fe3O4 absorber produced by pure chemical methods, and its wave absorption bandwidth can cover the 3 to 18 GHz frequency band, and the minimum reflection loss can reach -40 dB, and its performance has reached similar products with excellent performance on the market. It is more worth mentioning that this product is extracted from non-ferrous metallurgical waste slag, is a solid waste resource recycling, and has a simple remanufacturing process and huge industrialization potential.

[0064] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a microwave absorbing material, It is characterized in that The following steps are involved: The magnetite powder is subjected to ball milling, magnetic separation and heat treatment in sequence to obtain the microwave absorbing material; The magnetite powder is magnetite powder recovered from waste slag, and the average particle size of the product after ball milling is 0.5-20 μm.

2. The absorbing material according to claim 1, It is characterized in that The ball milling is wet ball milling, and the dispersant of the wet ball milling includes ethanol; the rotation speed of the ball milling is 200-300 r / min, and the ball milling time is 3-15 hours.

3. The absorbing material according to claim 2, It is characterized in that The grinding balls used for ball milling are large grinding balls, medium grinding balls and small grinding balls; the diameter of the large grinding balls is 8-12 mm, the diameter of the medium grinding balls is 5-7 mm, and the diameter of the small grinding balls is 2-4 mm; the mass ratio of the large grinding balls, medium grinding balls and small grinding balls is 1:9-11:18-22; the material-to-ball ratio of the ball mill is 1:10-30.

4. The absorbing material according to claim 1, It is characterized in that The intensity of the magnetic separation is 50 to 300 mT; Before the magnetic separation, the process also includes: dispersing the ball-milled product in water to obtain a dispersion.

5. The absorbing material according to claim 1, It is characterized in that The magnetic separation can be repeated 2 to 6 times.

6. The absorbing material according to claim 1, It is characterized in that The method also includes drying the product obtained by magnetic separation before the heat treatment, wherein the drying temperature is 75 to 85° C. and the drying time is 8 to 16 hours.

7. The absorbing material according to claim 1 or 6, It is characterized in that The temperature of the heat treatment is 500-900° C., the heat preservation time is 1-3 hours, and the heating rate to the temperature required for the heat treatment is 4-6° C. / min.

8. The absorbing material according to claim 1, It is characterized in that The magnetite powder comprises the following components in percentage by mass:

9. The microwave absorbing material prepared by the preparation method according to any one of claims 1 to 8, It is characterized in that It includes a magnetite phase and a pyroxene phase; the mass percentage of the magnetite phase in the absorbing material is 70-85%; The average particle size of the wave absorbing material is 0.5-20 μm.

10. The absorbing material according to claim 9 is Fe 3 O 4 Base absorbers are used in composite absorbing materials.

Citation Information

Cited By

  • Wave-absorbing material, preparation method therefor, and use thereof

    WO2026056501A1